2015
DOI: 10.1111/ajgw.12173
|View full text |Cite
|
Sign up to set email alerts
|

Vineyard irrigation scheduling based on airborne thermal imagery and water potential thresholds

Abstract: Background and Aims Mapping the spatial variability of vine water status within a vineyard is necessary for the efficient management of irrigation water. The objective of this study was to determine whether estimates of remotely sensed leaf water potential (Ψrem) could be employed as a precise tool for scheduling irrigation at the irrigation sector level throughout the season. Methods and Results Three irrigation treatments were applied in a 16‐ha commercial vineyard to analyse the performance of the proposed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
61
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(67 citation statements)
references
References 30 publications
4
61
0
2
Order By: Relevance
“…A linear NWSB was developed in this study for peach trees using all season data of two following years (Figure 2d). This NWSB was similar to those reported for other crops such as olive and sweet lime trees, but completely different than other crops (Table 4 [5,20,21,[34][35][36][37]). Mandarine and orange trees were the only crops that reported a higher intercept of the NWSB than peach trees [21].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…A linear NWSB was developed in this study for peach trees using all season data of two following years (Figure 2d). This NWSB was similar to those reported for other crops such as olive and sweet lime trees, but completely different than other crops (Table 4 [5,20,21,[34][35][36][37]). Mandarine and orange trees were the only crops that reported a higher intercept of the NWSB than peach trees [21].…”
Section: Discussionsupporting
confidence: 81%
“…Remote sensing technologies are a successful tool to accurately identify spatial heterogeneity and have been shown to have the capacity to monitor irrigation at orchard level [4,5]. The use of remote sensing in the assessment of crop water status through canopy temperature has had a long development history.…”
Section: Introductionmentioning
confidence: 99%
“…Such temperature anomalies impact the simulation of crop development and physiological processes and, therefore, need to be considered in crop system models. The canopy temperature of wheat is directly related to its water status [24][25][26][27][28]. We therefore hypothesize that environmental variables available from widely applied crop system models, such as daily transpiration and soil evaporation, allow for approximating wheat canopy temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…For hydrological applications, SfM provides information on microtopography and can be used to generate digital terrain models (DTMs) and digital surface models (DSMs) at unprecedented detail. Apart from their natural affinity to application in precision agriculture (Zhang and Kovacs, 2012) and for vegetation health and stress monitoring (Zarco-Tejada et al, 2012, 2013, a number of recent contributions have demonstrated the utility of UAVs in hydrological process studies, with snow depth retrieval (Vander Jagt et al, 2015), flood mapping (Feng et al, 2015), irrigation monitoring (Bellvert et al, 2016), and evaporation estimation (Hoffmann et al, 2016) all being explored.…”
Section: Unmanned Aerial Vehiclesmentioning
confidence: 99%